AI’s Impact on Access to Information in Democracies - Neylan, Julian (Politikon: The IAPSS Journal of Political Science, 2025)
One of the most urgent challenges facing democracies is a widening digital divide: wealthier groups will increasingly access expert verified information while lower income communities will not be given tools to navigate an online environment increasingly filled with convincing AI generated content. To safeguard democratic participation, we must democratize AI literacy and detection tools, and integrate civic education. Only by reinforcing these initiatives can democracy remain resilient in the age of AI.